Pengaruh Penggunaan Alat Peraga ROMA “Rompi Mamae” Terhadap Keterampilan Sadari dalam Mencegah Kanker Payudara pada Kader Kesehatan - Rahayu, Dini Dwi; Nur Cory'ah, Fitra Arsy; Gumilang Pratiwi, Intan (Indonesian Journal Publisher, 2025)
Background: Breast cancer remains a significant global health concern. According to the World Health Organization (WHO), by 2050, the number of new breast cancer cases is projected to increase by 38%, with a 68% rise in mortality, reaching an estimated 3.2 million new cases and 1.1 million deaths annually. In Indonesia, breast cancer is the most common type of cancer, with an incidence rate of 40.3 per 100,000 women and a mortality rate of 16.6 per 100,000 women. Alarmingly, approximately 70% of cases are diagnosed at an advanced stage due to low awareness of early detection. Data show that 90% of Indonesian women have never performed breast self-examination (BSE). This situation is exacerbated in regions such as Lenek Lauq Village, East Lombok Regency, where many health cadres lack sufficient skills in performing BSE. To address this issue, an innovative educational tool called